2018
DOI: 10.1097/mpa.0000000000001115
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of Integrating Yttrium-90 Radioembolization With Capecitabine-Temozolomide for Grade 2 Liver-Dominant Metastatic Neuroendocrine Tumors

Abstract: CapTemY90 is feasible and safe for grade 2 NETs. Toxicities were additive. Oncologic outcomes suggest synergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In total, prophylaxis was only used in 20.1% of the whole population (1,116/5,545). The employed prophylaxis included octreotide therapy (13 studies) [39, 61, 64, 65, 83, 92, 100, 102, 104, 111, 122, 128, 129] and somatostatin analogues (not specified; 2 studies) [99, 132]; however, in 86 studies, prophylaxis details were not reported.…”
Section: Resultsmentioning
confidence: 99%
“…In total, prophylaxis was only used in 20.1% of the whole population (1,116/5,545). The employed prophylaxis included octreotide therapy (13 studies) [39, 61, 64, 65, 83, 92, 100, 102, 104, 111, 122, 128, 129] and somatostatin analogues (not specified; 2 studies) [99, 132]; however, in 86 studies, prophylaxis details were not reported.…”
Section: Resultsmentioning
confidence: 99%
“…There are early phase 1 and 1b data on combining SIRT with everolimus and pasireotide, 75 and capecitabine-temozolomide. 76 These combination therapies hold promise and have so far proven safety. King et al 77 prospectively studied a combination of TARE and 7-day systemic infusion of 5-fluorouracil as a radiosensitizer in 34 patients with progressive NETLMs.…”
Section: Combination With Chemotherapymentioning
confidence: 99%
“…Y90 administration was performed on the dominant lobe on day 7 of the second cycle, with the remaining lobe treated on day 7 of the third or fourth cycle in patients with bilobar disease. 41 A median of eight cycles of chemotherapy were administered per patient, with nine patients requiring dose reductions or interruptions, and eight patients requiring eventual treatment cessation due to toxicities. Adverse events were additive, relative to known toxicity profiles for Y90 and capecitabine/temozolomide as individual therapies.…”
Section: Systemic Chemotherapymentioning
confidence: 99%
“…However, oncologic outcomes indicated synergy, and a proposed phase 2 trial aims to further investigate this treatment combination. 41…”
Section: Systemic Chemotherapymentioning
confidence: 99%